Pembangunan Dan Keberkesanan Aplikasi Pembelajaran Geometri Realiti Terimbuh (Learngeoar) Terhadap Keupayaan Visualisasi Ruang Dan Pencapaian Tajuk Ruang Dalam Kalangan Murid Tahun Dua - Nadzeri, Mohamad Basri (2024)
Learning geometry poses a challenge for primary school pupils, demanding an an understanding of abstract concepts and spatial visualization skills.Augmented Reality (AR) technology emerges as one of a promising solution to enhance conceptual understanding by providing visual representations of geometric shapes. This study aims to develop and evaluate the effectiveness of Augmented Reality Learning Application (LearnGeoAR) on spatial visualization ability and achievement in Space topic for year two pupils. The research design is based on Design and Development Research (DDR), comprising three main phases: need analysis, design and development and evaluation. In the need analysis phase, three expert mathematics teachers offer insights into the geometry learning environment through semi-structured interviews and questionnaire involving 220 pupils and 52 mathematics teachers which identifies challenges, perceptions about geometry and characteristics of the AR application developed for the Space topic. The design and development phase involve seven expert lecturers and teachers, along with 30 year-two pupils through alpha and beta testing to ensure the validity and reliability of the LearnGeoAR application. During the evaluation phase, a quasi-experimental pre- and post-test non-equivalent group design is employed, involving 61 year two pupils from two primary schools in Kerian District, Perak, with 31 pupils in the experimental group and 30 pupils in the control group.